Beyond dispersal versus philopatry? Alternative behavioural tactics of juvenile roe deer in a heterogeneous landscape. Issue 1 (26th September 2019) - Ducros, Delphine; Morellet, Nicolas; Patin, Rémi; Atmeh, Kamal; Debeffe, Lucie; Cargnelutti, Bruno; Chaval, Yannick; Lourtet, Bruno; Coulon, Aurélie; Hewison, A. J. Mark
Abstract : Although inter‐individual heterogeneity in many aspects of dispersal behaviour is widely reported, this key life‐history trait is predominantly modelled as a dichotomous state of philopatry versus dispersal. The increasing body of evidence for dispersal syndromes (i.e. a suite of correlated morphological, behavioural and life‐history traits associated with dispersal) implies substantial but, to date, undocumented individual heterogeneity in behavioural tactics during dispersal. Using a large sample (n = 154) of GPS monitored juvenile roe deer Capreolus capreolus, we evaluated among‐individual behavioural heterogeneity in dispersal tactics, and the individual and environmental drivers of these alternative tactics. We developed a sequential three‐stage decision tree based on space use stability, exploration events and the directionality of movement. We identified six discrete alternative behavioural tactics during the dispersal period which were characterised by different timing, amplitude and duration in movement: slightly less than half of the deer were sedentary, either 'strictly philopatric' or 'explorers', which subsequently settled on their natal range; around 40% dispersed ('classic dispersal'), of which, one in six subsequently aborted, moving back to their natal range ('aborted dispersal'); finally, around 15% expressed either a 'progressive dispersal' tactic, gradually moving away from their natal area to settle elsewhere, or a 'multi‐range' tactic. The propensity to express an alternative dispersal tactic was strongly influenced by an individual's local environment. In particular, when landscape heterogeneity, resource quality and human‐related disturbance in the natal range were low, individuals were 1) more likely to adopt the alternative tactics of either progressive dispersal or multi‐ranging, but 2) also more likely to abort their dispersal attempt. Our work indicates that natal dispersal is likely not a single uniform behaviour, but that individuals may adopt a variety of alternative movement tactics which are likely governed by different selection pressures, with potentially important impacts for population dynamics and functioning.